Unfair competition – an attack on the patrimonial rights of natural and legal persons - V. Ursu; E. Musteata (Аналітично-порівняльне правознавство, 2024)
The subjects of the economic activity, whether they are natural persons or legal entities, are obliged to exercise their activity in good faith, according to honest usages, respecting the interests of consumers and the requirements of fair competition.